Jejunojejunal intussusception of a sutured enterotomy site after takedown and primary repair of persistent enterocutaneous fistula: a case report. Issue 9 (20th September 2022) - Marlor, Derek; Noor, Sibat; Beck, Justin; Taghlabi, Khaled M; Al-Kasspooles, Mazin
Abstract: Enterocutaneous fistula (ECF) is a common complication of many abdominal surgeries. Although most ECF resolve spontaneously, there are many factors that can lead to persistence of the fistula. Management of persistent enterocutaneous fistula usually involves surgery with recurrence of fistula being the most common complication. Here we describe a case of 67-year-old female who presented with intussusception following repair of a persistent enterocutaneous. Given the rare finding of intussusception in adults, this case report presents an interesting complication.